Vivaldi Antenna Arrays Feed by Frequency-Independent Phase Shifter for High Directivity and Gain Used in Microwave Sensing and Communication Applications - Jiwan Ghimire (Sensors, 2021)
This paper describes a novel feed system for compact, wideband, high gain six-slot Vivaldi antenna arrays on a single substrate layer using a unique combination of power splitters based on binary T-junction power splitter topology, frequency-independent phase shifter, and a T-branch. The proposed antenna system consists of six Vivaldi antennas, three on the left, and three on the right arm. Each arm connects with T-junction power divider splitter topology, given that the right arm is linked through a frequency-independent phase shifter. Phase shifters ensure that the beam is symmetrical without splitting in a radiating plane so that highly directive radiation patterns occur. The optimal return losses (S-parameters) are well enriched by reforming Vivaldi’s feeding arms and optimizing Vivaldi slots and feeds. A novel feature of our design is that the antenna exhibits the arrangements of a T-junction power splitter with an out-of-phase feeding mechanism in one of the arms, followed by a T-branching feeding to even arrays of proper Vivaldi antenna arrangement contributing high realized gain and front-to-back ratio up to 14.12 dBi and 23.23 dB respectively applicable for not only ultra-wideband (UWB) application, also for sensing and position detecting. The high directivity over the entire UWB frequency band in both higher and lower frequency ranges ensures that the antenna can be used in microwave through-wall imaging along with resolution imaging for ground penetration radar (GPR) applications. The fabricated antenna parameters are in close agreement with the simulated and measured results and are deployed for the detection of targets inside the voids of the concrete brick.